"A target model of the mental health and psychosocial support system" As a response to the devastating impact of war in Ukraine - Zbitnieva, Оксана; Chaban, Олег; Omelyanovich, Віталій (Psychosomatic Medicine and General Practice, 2024)
According to the World Health Organization, about 22% of the population of Ukraine is at risk of mental disorders. The war affects not only mental health but also social and economic living conditions. The response to these challenges was the development of the target model “System in the field of mental health and psychosocial support”, which was carried out by the team of authors of the Coordination Center for Mental Health under the Cabinet of Ministers of Ukraine within the framework of the All-Ukrainian Mental Health Program initiated by Olena Zelenska. The target model defines the national direction for creating an optimally functioning integrated mental health and psychosocial support system in Ukraine. The purpose of the target model was to describe a new system of mental health support, to create legislation on mental health in a broad sense that goes beyond health care, and to introduce relevant changes in all spheres of society. The target model provides a comprehensive overview of the envisioned national mental health system in Ukraine, which includes promotion, prevention, further development of the mental health service network, and involvement of all relevant sectors at the national and local levels, and aims to ensure good coordination between all stakeholders involved in addressing the wide range of mental health needs of the Ukrainian population during the war and recovery period. According to this goal, the main postulates of the target model and four main tasks were formulated. Ways to achieve this goal were identified, and recommendations for the implementation of strategic tasks at the national, regional and local levels were carefully described.